CSE-Induced ER-Mitochondria Crosstalk Promotes Oxidative Stress and Impairs Bronchial Contractile Response - Jorge Rodríguez-Pérez; Rosa Andreu-Martínez; Leila Pérez-Sánchez; Ana Hernández-García; Cecilia Muñoz-Calleja; Ángel Cogolludo; María J. Calzada (Antioxidants)
Chronic obstructive pulmonary disease (COPD), whose main risk factor is cigarette smoking, is among the most prevalent diseases worldwide. Previous studies have shown that cigarette smoke extract (CSE) can directly affect pulmonary artery function independently of hypoxia resulting from the airway obstruction. In addition, CSE also affects bronchial smooth muscle, leading to airway hyper-responsiveness. However, its specific impact on the contractile machinery of this compartment remains unclear. In this study, using in vitro experiments with human bronchial smooth muscle cells (hBSMCs), we found that CSE exposure disrupted calcium homeostasis, increased ROS and lipid peroxidation, and reduced cell antioxidant defenses. Furthermore, CSE exposure altered the cell contractile apparatus by decreasing key cytoskeletal proteins and impairing actin dynamics, potentially contributing to the dysregulated contractile response of cells. Notably, these effects were significantly attenuated by antioxidant drugs such as mitoTEMPO and N-acetylcysteine, as well as by the inhibition of the endoplasmic reticulum (ER) calcium channels with 2-aminoethoxydiphenyl borate (2-APB). More importantly, mitoTEMPO partially restored the contractile response of bronchus upon CSE challenge. Collectively, our findings give evidence that CSE-mediated increase in ROS and intracellular calcium contribute to cytoskeletal disruption and functional impairment in airway smooth muscle. Moreover, these results also point to potential therapeutical approaches for mitigating the harmful effects of cigarette smoke in the lung.